Efektifitas Edukasi Kesehatan Tentang Penggunaan Skrining Pre Eklamsia Terhadap Keterampilan Kader Dalam Mendeteksi Ibu Hamil Resiko Tinggi di Posyandu Wilayah Kerja Puskesmas Tanta - Setyaningsih, Agus; Zulliati, Zulliati; Hidayah, Nurul (Jurnal Rumpun Ilmu Kesehatan, 2024)
One of the causes of MMR and AKB in Indonesia mostly occurs due to hypertension (25%). Prevention of preeclampsia is by screening pre-eclampsia in pregnant women at >20 weeks gestation. The role of cadres is very important in helping midwives to detect high-risk pregnant women. The purpose of the study was to determine the effectiveness of health education on the use of pre-eclampsia screening on cadre skills in detecting high-risk pregnant women in posyandu working areas of Tanta Health Center. This research method includes experimental research using pre-experimental designs type Pretes-Posttest Design. The population is posyandu cadres for pregnant women and toddlers in the Tanta Health Center work area as many as 80 people with sampling techniques with Quota Sampling as many as 40 respondents. The data analysis technique uses the Wilcoxon signed Rank test. The results showed that there was a difference between cadres' skills in detecting high-risk pregnant women before and after health education about the use of pre-eclampsia screening.